PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA MANIPULATIF PADA PEMBELAJARAN MATEMATIKA DI KELAS V - Farida, Ida; Tampubolon, Budiman; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the use of manipulative media to improve student learning outcomes in Grade V Mathematics learning at West Pontianak 04 Public Elementary School. This type of research is classroom action research. The research subjects were fifth grade students of SD Negeri 04 Pontianak Barat. The research method used is descriptive. Data collection techniques used are direct observation techniques and documentation observation techniques. While the data collection tools are observation sheets and test instruments. Data collected is analyzed by calculating percentages and averages. The results of the study showed an increase in Mathematics learning outcomes of fifth grade students of SD Negeri 04 Pontianak Barat after using manipulative media. The results achieved in this study were (1) the preparation of the first cycle RPP of 3.02 increased in cycle 2 to 3.19 and increased in cycle 3 to 3.68. The increase in the implementation process in the first cycle of 3.02 increased in cycle 2 to 3.37 and in cycle 3 to 3.69. Learning outcomes also increased from an average of 48.42 in cycle 1 to 72.37 in cycle 2 and increased in cycle 3 to 92.11.Â Keywords:Learning Outcomes, Manipulative Media, and Mathematics